Women Strengthening Through Information Technology Literacy in Tourist Village - Sujarwo, Sujarwo; Kusumawardani, Erma; Tristanti, Tristanti; Santi, Fitta Ummaya (Universitas Negeri Semarang, 2021)
Women have positive potentials that support their strategic role in development. This research aims to analysis implementing information technology literacy model guidelines in empowering women through community-based education and how increasing the knowledge, skills, and awareness of women in managing the productive potential of information technology-based environments. By the research and development method or Research amp; Development, this research tries to produce a product and test the effectiveness of the product in accordance with development goals. Women#39;s empowerment activities through information technology including providing information technology-based entrepreneurship motivation, forming business groups, training in information technology-based business management, managing businesses and assisting business groups. Data was collected using the method of observation and interview. The collected data were analyzed with qualitative descriptive. The findings of the study are; 1) implementation program which includes: a. preparation for program implementation which includes program socialization, selection of participants, program objectives, materials, strategies, media, teaching materials, assessment, b. implementation of programs, providing information technology-based entrepreneurship, information technology-based business management training, managing businesses and assisting business groups, c. evaluating the implementation of the program by making direct observations during the process, 2) increasing the knowledge of the culinary group.